Membrane domains in lymphocytes - from lipid rafts to protein scaffolds. - Harder, T; Engelhardt, K (2004)
Lateral compartmentalization of the plasma membrane into domains is a key feature of immune cell activation and subsequent immune effector functions. Here, we will review the high diversity of membrane domains, ranging from elementary lipid rafts, envisioned as dynamic and small domains (in the tens of nm), to relatively stable microm-scale membrane domains, which form the immunologic synapse of T lymphocytes. We will discuss the relationship between these different types of plasma membrane domains and how raft lipid- and protein-controlled interactions and cell biological processes cooperate to generate functional domains that mediate lymphocyte activity.